2017
DOI: 10.1002/ece3.2717
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment, sexual dimorphism, and brain size in sticklebacks

Abstract: Evidence for phenotypic plasticity in brain size and the size of different brain parts is widespread, but experimental investigations into this effect remain scarce and are usually conducted using individuals from a single population. As the costs and benefits of plasticity may differ among populations, the extent of brain plasticity may also differ from one population to another. In a common garden experiment conducted with three‐spined sticklebacks (Gasterosteus aculeatus) originating from four different pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 51 publications
(88 reference statements)
5
26
1
2
Order By: Relevance
“…In comparison to field sampling across the breeding cycle, this experiment conducted under controlled environmental conditions allowed us to evaluate to what degree variation in brain SSD is attributable to developmental, sex-specific or populationspecific sources. As to the latter, large population differences that are constant over all three sampling points would provide evidence for the importance of fixed differences in SSD among populations, and support the hypothesis that the large variance in brain SSD among stickleback populations observed in earlier studies (Herczeg et al, 2015;Kotrschal et al, 2012a;Samuk et al, 2014;Toli et al, 2017) is mainly attributable to population differentiation (see Toli et al, 2017). On the contrary, constant ( parallel) changes in brain SSD over different sampling periods in all replicate populations would provide strong evidence for a developmental component to brain SSD, and indicate that the large variance in brain SSD observed in earlier studies (see above) could owe to differences in timing of sampling relative to the breeding cycle.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…In comparison to field sampling across the breeding cycle, this experiment conducted under controlled environmental conditions allowed us to evaluate to what degree variation in brain SSD is attributable to developmental, sex-specific or populationspecific sources. As to the latter, large population differences that are constant over all three sampling points would provide evidence for the importance of fixed differences in SSD among populations, and support the hypothesis that the large variance in brain SSD among stickleback populations observed in earlier studies (Herczeg et al, 2015;Kotrschal et al, 2012a;Samuk et al, 2014;Toli et al, 2017) is mainly attributable to population differentiation (see Toli et al, 2017). On the contrary, constant ( parallel) changes in brain SSD over different sampling periods in all replicate populations would provide strong evidence for a developmental component to brain SSD, and indicate that the large variance in brain SSD observed in earlier studies (see above) could owe to differences in timing of sampling relative to the breeding cycle.…”
Section: Introductionsupporting
confidence: 71%
“…The sex-specific increase in brain size over the breeding cycle was similar in all four replicate populations used in this study, confirming the ubiquity of a developmental component to brain SSD. This finding also excludes geographic variation as the unique source for the observed between-population variation in the degree of brain SSD (Herczeg et al, 2015;Kotrschal et al, 2012a;Samuk et al, 2014;Toli et al, 2017). In essence, we conclude that studies using snapshot sampling for brain size measurements from different populations at different time points over the reproductive season need to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Salmon living in enriched tanks were faster in escaping mazes and showed increased expression of a pro-neurogenic gene (Salvanes et al, 2013). There is conflicting evidence for the effect of enrichment on brain size in fish, with enrichment having no effect on three-spined sticklebacks, but decreasing brain size in eastern mosquitofish (Toli et al, 2017;Turschwell and White, 2016). Early studies in D. melanogaster have found that changing the social milieu affects the size of brain structures, with social isolation leading to decreased sizes and numbers of Kenyon cell fibers (Barth and Heisenberg, 1997;Heisenberg et al, 1995;Technau, 1984).…”
Section: Introductionmentioning
confidence: 99%